Nurses’ Professional Quality of Life (Medico Legal Update, 2019)
Background/Objectives: This study is a descriptive research study to identify factors affecting quality of professional lives of nurses.Method/Statistical Analysis: The subjects of this study were 177 nurses working in a general hospital in Korea, and the data collection was from February 01, 2018 to February 26, 2018. The collected data were analyzed by descriptive statistics, t-test, ANOVA, Pearson’s correlation and multiple regression analysis.Findings: As a result of the study, Quality of professional lives of nurses and Emotional labor(r=-.114, p=.016) showed negative correlation, and Emotional intelligence(r=.274, p=.000) showed significant positive correlation. Among emotional intelligence, self emotional appraisal(?=-.043, p=.000) and the use of emotion(?=-.394, p=.007) were found to affect the quality of professional lives of nurses.Improvements/Applications: In conclusion, strategies for minimizing emotional labor and improving emotional intelligence are needed to improve the quality of professional life.